Berebut Manisnya Tebu Studi tentang perolehan akses program bantuan tebu di Lhokcane , Kab. Bener Meriah, Provinsi Nangroe Aceh Darussalam - Galeh Prabowo (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2018)
An Introduction of sugarcane is apparently able to create an interesting social phenomenon among peasants in Lhokcane. It has led to the entry of commodity competition in access to land and sugarcane assistance program. The reality of it is about the emergence of inequality both ownership and control over economic resources. Therefore, this paper aims to understand the process of acquisition of land and access to assistance programs cane. Key words : sugarcane, access, land, and inequality